GENETIC CONTROL AND ASSOCIATION AMONG ECONOMIC TRAITS IN SAHIWAL CATTLE: A REVIEW - Z. Rehman; M. S. Khan; M. S. Rehman; Faiz ul Hassan (Journal of Animal and Plant Sciences, 2013)
Sahiwal cattle breed of Pakistan is one of the best zebu cattle breed that can potentially play the same role as Holstein for tropical environment. The lifetime story of Sahiwal cattle in Pakistan represents a genetic resource unaltered and awaiting genetic improvement to satisfy the local and international needs of milk and meat. The genetic factors are generally influenced the Sahiwals' performance and the supporting reports from other breeds in the region are also presented for comparison. The performance traits reviewed were age at first calving, milk yield, lactation length, dry period, calving interval and service period of Sahiwal cows. The genetic parameters such as heritability and genetic correlations are helpful in determining the selection strategy for a single or multiple selection objectives. The repeatability estimates are used in determining the amount of culling that can be practiced on the basis of initial records. The genetic correlations among various performance traits have been reported by various workers but agreement between any two studies for any two traits is difficult to find. Genetic trend was close to zero. However, due to appreciable additive genetic variation, it was suggested that genetic improvement in traits like milk yield was possible.
Keywords: Sahiwal cattle; milk yield; repeatabilty; heritability; genetic correlation